Temperature-regulated expression of outer membrane proteins in Shigella flexneri - Harikrishnan, H; Ismail, A; Singh, KKB (Biomed Central Ltd, 2024)
Background: Bacteria exist widely in a diversity of natural environments. In order to survive adverse conditions such as nutrient depletion, biochemical and biological disturbances, and high temperature, bacteria have developed a wide variety of coping mechanisms. Temperature is one of the most important factors that can enhance the expression of microbial proteins. This study was conducted to investigate how outer membrane proteins (OMPs) of the bacterium Shigella flexneri respond to stress, especially during fever when the host's body temperature is elevated. Methods: OMPs of S. flexneri ATCC 12022 and clinical isolate SH057 were extracted from an overnight culture grown at 37, 38.5, and 40 degrees C. Comparisons of the expressed proteins under the different growth conditions were based on equal numbers of bacterial cells loaded in the SDS-PAGE gels. Separated proteins were stained with Coomassie brilliant blue. Selected proteins showing increased expression at 38.5 and 40 degrees C were characterized by performing MALDI-ToF-ToF. Results: Different degrees of expression were demonstrated for different proteins expressed at 37 degrees C compared to 38.5 and 40 degrees C. The proteins with molecular sizes of 18.4, 25.6, and 57.0 kDa showed increased expression level at increasing temperature and were identified as Dps, WrbA, and PepA, respectively. Conclusion: This study revealed that strains of S. flexneri respond at the proteomic level during stress caused by elevated temperature by decreasing the expression of proteins, maintaining the level of important proteins, or enhancing the levels of proteins presumably involved in survival and virulence.